Managerial versus production wages: Offshoring, country size and endowments - Sebastian Benz; Wilhelm Kohler (University of Tübingen, Faculty of Economics and Social Sciences, 2011)
We explore the role of trade in differentiated final goods as well ollshoring of tasks for inequality both within and between countries. We emphasize the distinction between managerial and production labor. Managerial labor is a fixed input while production labor is a variable input. Following Grossman & Rossi-Hansberg (2010b) we assume that production labor is composed of tradable tasks, with Marshallian economies of scale on the task level. We first identify the key determinants of income distribution in a world where trade is restricted to final goods. We then allow for trade in production tasks, driven by country size as well as relative endowment with managerial and production labor. If the two countries are of equal size and if their relative endowments are not too different, then the task trading equilibrium features equalization of production wages, although the pattern of task trade and managerial wages are indeterminate. For differences in relative endowments beyond a certain threshold level, the trading equilibrium is unique and features one-way trade in line with comparative advantage. Relying on numerical simulations we show that international inequality is affected in a non-monotonic way by the cost of task trade. Comparing orders of magnitude we conclude that offshoring between similar countries only has a small positive effect on the managerial wage premium, compared to offshoring between countries with a different relative endowment.
urn:nbn:de:bsz:21-opus-56848
Keywords: F12; F16; F23; 330; Offshoring; Economies of Scale; Income Distribution; International Inequality; Offshoring; Einkommensverteilung; Produktdifferenzierung; Außenhandelsliberalisierung; Anforderungsprofil; Produktionsfaktor; Skalenertrag; Industriearbeit; Handelbares Gut; Führungskräfte; Nicht-handelbares Gut; Lohnstruktur; Theorie